Biological degradation of Reactive Black 5 dye by yeast Trichosporon akiyoshidainum - Martorell, María Martha; Pajot, Hipolito Fernando; Castellanos, Lucia Ines (Journal of Environmental Chemical Engineering)
The textile dyeing and other industries use an extensive amount of azo dyes. Their effluents are specifically colored and could cause severe damage to the environment. The anaerobic treatment of textile dying effluents could generate carcinogenic aromatic amines. For this reason, in the recent years yeasts have become a promising alternative, combining unicellular growth with oxidative mechanisms. This work reports the oxidative Reactive Black 5 (RB5) biodegradation mechanism by Trichosporon akiyoshidainum HP 2023, isolated from a non-contaminated environment and extensively studied for its exceptional decoloration abilities on azo dyes. Several analytical techniques (HPLC, FTIR, GC–MS, UV–vis) were used as to monitor the dye-decoloration process and the enzyme produced during biodecoloration. Starting with 200 mg L−1 of RB5, at 12 h, 89% color removal and a shift from dark blue to purple was observed, at 24 h no color was visible. Also, a decrease of aromatic amines and total aromacity (71 and 75%, respectively) was observed and biomass presented no color. The mechanism is driven by phenol oxidase and peroxidase enzymes, as they were no present in cultures without dye. During decoloration, at 15 h both enzymes reached it maximum activity levels, 353 UL−1 for phenol oxidase and 2750 UL−1 for peroxidase. The two-stages proposed mechanism involves the formation of a purple-colored quinone with an azo bond, which is subsequently degraded, finally the complete disappearance of color is achieved. These results make Trichosporon akiyoshidainum HP 2023 a promising tool for dye removal treatment of colored textile effluents. Fil: Martorell, María Martha. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas. Centro Científico Tecnológico Conicet - Tucumán. Planta Piloto de Procesos Industriales Microbiológicos; Argentina Fil: Pajot, Hipolito Fernando. Consejo Nacional de ...